Management of diabetes mellitus in the era of COVID-19 - Paz Ibarra, Jose (2020)
Diabetes mellitus is a worldwide public health problem which is associated with an increase in morbidity and mortality in the affected population due the development of micro and macrovascular complications. Currently, the SARS-CoV-2 epidemic is constantly increasing in many countries, causing the collapse of healthcare systems by leading to an increased demand for care, as well as an upsurge in the associated mortality. Available reports describe that patients with diabetes mellitus have an increased risk of unfavorable progression, development of complications and even an increase in mortality rate. Some physiological mechanisms have been proposed to try to explain this special evolution in patients with diabetes. Given the presence of 2019 coronavirus disease in our country and an important group of high-risk patients, a review of the pathophysiology and management considerations of this association is presented.